Metode Multi Attributive Border Approximation Area Comparison (MABAC) Untuk Penilaian Kinerja Dalam Pengelolaan Alokasi Dana Desa (ADD) - cucu - handayani; Adi Muhamad Muhsidi; Nur Isti Khomalia (Jurnal ICT : Information Communication & Technology, 2021)
The Village Fund Allocation is one income proceed for the Village Revenue and Expenditure Budget of the rural government. For the implementation of financial governance, the Department of Community and Rural Empowerment does not yet have a performance appraisal system in managing the Fund Allocations. The Performance Appraisal System which is developed in this study aims to determine the optimality of rural governments in managing the Village Fund Allocation. The research methodology used in the study is MABAC (Multi-Attributive Border Approximation Area Comparison), a multi-alternative decision type. This method was chosen because of its stability and consistency in the solutions of decision making, compared to other decision support methods. The study was carried out on 11 villages with predetermined criteria data. From this data, an analysis is carried out resulting in values of performance assessment as well as the optimality of Fund Management.